IDENTIFIKASI KESULITAN-KESULITAN YANG DIALAMI SISWA KELAS VIII C SMPN 3 MAJA DALAM MENYELESAIKAN SOAL TEKS BERITA - Widyananda, Siti Wafa (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
News text is one of the lessons that students must master in Indonesian subjects. Even though students in general are familiar with the news in their daily life, this does not necessarily mean that they are easy to master. In an effort to measure the level of student understanding of the news text learning material, learning evaluation is an important thing that must be carried out. However, the complexity of the knowledge and skills that students must master in learning news texts becomes an obstacle in obtaining good learning outcomes in learning news texts. This study aims to identify the various difficulties experienced by students in solving news text questions. The method used in this research is a qualitative descriptive method that describes the object of research as it is. The subjects in this study were 24 students of class VIII C of SMPN 3 Maja. The instrument used was the students' final test results in learning news texts. Through this research, the research results obtained regarding the various difficulties of students in solving news text questions based on two factors, namely internal factors and external factors. Internal factors relate to student difficulties in answering questions related to analyzing news elements, analyzing news language rules, and providing responses to news content. This difficulty is caused because the three questions in question are at a high level thinking ability. The external factors relate to teachers, students, facilities and infrastructure, and the environment.